2020
DOI: 10.1038/s41598-020-69499-6
|View full text |Cite
|
Sign up to set email alerts
|

Roniciclib down-regulates stemness and inhibits cell growth by inducing nucleolar stress in neuroblastoma

Abstract: Neuroblastoma, an embryonic tumor arising from neuronal crest progenitor cells, has been shown to contain a population of undifferentiated stem cells responsible for the malignant state and the unfavorable prognosis. Although many previous studies have analyzed neuroblastoma stem cells and their therapeutic targeting, this topic appears still open to novel investigations. Here we found that neurospheres derived from neuroblastoma stem-like cells showed a homogeneous staining for several key nucleolar proteins,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 83 publications
0
5
0
Order By: Relevance
“…Exosomes for immunofluorescence analysis were resuspended in 100 µL 1× PBS for Cytospin cell preparation and incubated with anti-GD2 mAb (1:500; secreted from hybridoma cell line 14.G2, a generous gift by R.A. Reisfeld, The Scripps Research Institute, La Jolla, CA, USA), followed by a specific secondary antibody conjugated with Alexa 488 (green). Immunofluorescence analysis was performed as previously described [ 55 ]. Results were photographically documented using fluorescence microscope Axio Imager M2 (Carl Zeiss, Oberkoche, Germany).…”
Section: Methodsmentioning
confidence: 99%
“…Exosomes for immunofluorescence analysis were resuspended in 100 µL 1× PBS for Cytospin cell preparation and incubated with anti-GD2 mAb (1:500; secreted from hybridoma cell line 14.G2, a generous gift by R.A. Reisfeld, The Scripps Research Institute, La Jolla, CA, USA), followed by a specific secondary antibody conjugated with Alexa 488 (green). Immunofluorescence analysis was performed as previously described [ 55 ]. Results were photographically documented using fluorescence microscope Axio Imager M2 (Carl Zeiss, Oberkoche, Germany).…”
Section: Methodsmentioning
confidence: 99%
“…Interestingly, treatment of neuroblastoma cells with Roniciclib, which induced cell differentiation and impaired neurospheres formation, also inhibited the expression of nucleolar nucleolin and of CSC markers such as CD44v6 and CD114 [ 177 ].…”
Section: Role Of Nucleolin On Stemness Pluripotency and Differentmentioning
confidence: 99%
“…Importantly, in limiting the dilution functional assay it was shown that sorted nucleolin + triple negative breast cells were more tumorigenic in NOD scid gamma mice than nucleolin low/cells, evidencing that cell surface nucleolin per se enables the selection of efficient tumorigenic cells [14]. Interestingly, treatment of neuroblastoma cells with Roniciclib, which induced cell differentiation and impaired neurospheres formation, also inhibited the expression of nucleolar nucleolin and of CSC markers such as CD44v6 and CD114 [177].…”
Section: Role Of Nucleolin On Stemness Pluripotency and Differentiation: A Potential Target For Broad Anticancer Therapymentioning
confidence: 99%
“…Very recently, it has been reported that roniciclib is active also on NB stem cells, which are a population of undifferentiated cells leading to an unfavorable prognosis. Ognibene et al demonstrated the anticancer effects of the compound on neurospheres derived from NB stem-cell-like and in an orthotopic NB mouse model [ 37 ].…”
Section: Stk Inhibitorsmentioning
confidence: 99%